Storage Conditions Fruits & Vegetables - Gast, Karen L. B. (My University, 1991)
This publication describes how to store fruits and vegetables after they are harvested to reduce loss.
MF978_1991_03
Keywords: MF978; Equipment and Structures; Fruits and Vegetables; MF